EFEKTIVITAS APLIKASI KAHOOT SEBAGAI MEDIA PEMBELAJARAN DALAM MENGHADAPI ERA SOCIETY 5.0 - Harahap, Asriana (PIONIR: JURNAL PENDIDIKAN, 2023)
Facing the era of society 5.0, every educator seeks suitable techniques to deal with the era of society 5.0 in the applied learning process, one of which is by using Kahoot as a medium in the teaching and learning process. Kahoot itself is a platform that offers a variety of interesting and educative features, with offers that are quite eccentric, making this application very popular in supporting the learning process. Using this kahoot application to determine the effectiveness of using kahoot as a learning medium in dealing with the era of society 5.0 at SDIT Darul Hasan. This type of research is quantitative with an experimental method in the form of a quasi-experimental (quasi-experimental). Based on the results of the study, it can be seen that the results of the control class obtained a pretest value of 34.7 and posttest 39.7. The obtained value is then calculated N-Gain and obtained an N-Gain score of 0.07 in the low category. In the experimental test, the pretest value was 56.6 and the posttest was 70. The value obtained was then calculated as an N-Gain of 0.34 in the medium category.